2017
DOI: 10.37358/rc.17.5.5590
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Heavy Metal Ions (As, Pb, Cd) and Zinc Mineral (Zn) in Humans and Cows Milk in Bitlis (Turkey)

Abstract: Human�s milk and cow�s milk fed-infants, long before the mother is exposed heavy metals are potentially dangerous for both mother and baby. Concentrations of toxic heavy metals (Pb, Cd, As) and major nutritional trace element (Zn) which collected center Bitlis, Tatvan and various villages in the 75 volunteer nursing mothers received 6 months after the birth human�s milks and 75 cow milks were analyzed. This study was measured by Inductively Coupled Plasma-Mass Spectrometer. Work was measured in accredited labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The concentrations of heavy metals may vary widely depending on exposures. The most common source of lead is the exhaust gases of vehicles [ 6 , 7 ]. Researchers have shown that lead can pass by maternal way to fetus and by milk to infants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrations of heavy metals may vary widely depending on exposures. The most common source of lead is the exhaust gases of vehicles [ 6 , 7 ]. Researchers have shown that lead can pass by maternal way to fetus and by milk to infants.…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic is a heavy metal naturally found in the earth and taken up to metabolism by contaminated water and plants. Prolonged exposure to arsenic in the infants can lead to arsenic poisoning and cancer risk [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%